Landscape Variation: Language Policy in Public Space in Makassar City - Hasriani, Hasriani; Sofyan, Ryan Rayhana (PT ARRUS Intelektual Indonesia, 2023)
Prioritize Indonesian, Master Foreign Languages, Preserve Regional Languages ​​is a mandate from Law No.24/2009 which indicates that as Indonesians we are encouraged to use the unified language in public spaces and communications. The problem in this study is how to use the form and function of the language landscape used in naming roads, apartments, hotels and places to eat/drink in the city of Makassar, so this study aims to describe the form and function of the language landscape used. This research is a qualitative descriptive research. The data in this study are street names, apartments, hotels and places to eat/drink in public spaces in the city of Makassar. The collection of research data was carried out using observation, reading, recording, and data classification techniques. Research data were analyzed using qualitative data analysis techniques using an objective approach. The results of the study show that variations in the language landscape based on language policies in public spaces in the city of Makassar consist of 8 types, namely Indonesian, Bugis, Makassarese, other foreign languages, Indonesian and Makassar languages, Indonesian and Bugis languages, Bugis languages ​​and Indonesian languages. Makassar, English and Indonesian. Based on the findings, it is suggested that the participation of all policy holders is urgently needed so that Indonesian and regional languages ​​are not dominated by English and other languages. Apart from that, the awareness of the Indonesian people needs to be built to prioritize the Indonesian language, and to preserve regional languages ​​in terms of naming in public spaces.